EFEKTIVITAS HARA MAKRO DAN MIKRO TERHADAP PERTUMBUHAN TANAMAN JAGUNG (Zea mays L.) - Sumiyati Tuhuteru (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2018)
Nutrient absorption in plants must be complex. Plants were able to produce optimum productivity, if the land grew the plant had a good fertility rate. The elements were most needed by plants to complete their life cycles were elements of N, P, and K. The purpose of this research was to estimate soil fertility to biological nutrition. The research was conducted in September until November 2017 at Green House of STIPER Petra Baliem Wamena, Papua. The treatments were assigned in Randomized Complete Design with a combination of fertilization, namely:Control (Without Treatment (K0), without N (PK), without P (NK), without K (NP), and complete fertilizer (NPK). The data was analyzed by using Anova with α = 5%, then followed by DMRT α 5%. The results showed that NK treatment gave a good effect for plant growth especially on plant height and ratio of plant leaf area. While, NP treatment gave a good influence to plant physiological properties, such as plant chlorophyll content and plant rate of assimilation.Keywords: effectiveness, hara, mayze